Cost analysis on non-surgical and surgical therapy for the management of residual pockets of periodontitis patients in Faculty of Dentistry Universiti Teknologi MARA: a pilot study / Nurul Qamar Salehuddin, Budi Aslinie Md Sabri and Farha Ariffin - Salehuddin, Nurul Qamar; Md Sabri, Budi Aslinie; Ariffin, Farha (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
This study aims to quantify and analyze the cost distribution of periodontal intervention that includes nonsurgical and surgical therapy in residual pockets management. Immediately after initial cause-related therapy (ICRT), subjects were allocated into two treatment groups: non-surgical (NS) or surgical (S) therapy. Clinical and cost data were recorded at baseline (Phase I) and periodontal review (Phase II). Direct and indirect cost distribution were estimated from patients' perspective and recorded in Ringgit Malaysia (RM) using activity-based costing methods. Indirect cost was calculated via productivity loss. The total average cost was RM1115.68 for the NS group and RM4558.28 for the S group. 46% and 66%of these were attributed to indirect cost while 54% and 34%to direct cost in NS and S groups respectively. Treatment charges and productivity lost attributed to the highest cost distribution in direct and indirect cost respectively. In conclusion, the cost of management of residual pockets in postgraduate periodontic clinic, Faculty of Dentistry UiTM was considered substantial and comparable to other non-communicable diseases and higher compared to management by government-based Periodontic Specialist clinics in Malaysia. These findings may assist in cost-reduction strategies and further justify the need for early detection and prevention of further disease progression.